Ancient Jerusalem’s Rural Food Basket - Edelstein, Gershon (The Biblical archaeology review, 1982)
Until recently, archaeology—or at least Near Eastern archaeology—has been regarded primarily as a historical science. Its focus was history and particularly political history—kings and kingdoms, battles and destructions, the rise and fall of civilizations. That focus has now shifted somewhat. It is difficult to put a date on the change because it has occurred […]